Visual analogies : Representation of the design process and its application in the field of education - Bravo, Úrsula (Base Diseño e Innovación, 2016)
In recent years, design thinking has been understood and spread as a method of creative problem solving, available for professionals of other disciplines, with the purpose of encouraging creative thinking, the identification of problems and the development of solutions (Johansson-Sköldberg et al., 2013; Dost, 2011; Hassi & Laakso, 2011).